Off-resonance surface plasmon enhanced spontaneous emission from CdTe quantum dots - BRADLEY, LOUISE; RAKOVICH, YURY; GOUNKO, IOURI (My University, 2006)
Surface plasmon (SP) enhanced photoluminescence (PL) from CdTe quantum dots (QDs) on monolayers of Au nanoparticles is investigated under both resonant and nonresonant conditions. Enhancement of the QD PL intensity is observed when the emission spectrum is redshifted with respect to the SP absorption resonance. Coupling to the SPs results in a redshift and broadening of the PL spectrum, and an increase in the PL decay rate. The largest coupling is observed for QD monolayers with peak emission at 667?nm, producing a ten fold increase in PL intensity. No change in PL intensity and decay rate is observed at the SP resonance.
PUBLISHED
This paper was selected for inclusion in the Virtual Journal of Nanoscale Science and Technology 15, 2 (2007).
Keywords: Optics; plasmons